2016
DOI: 10.3354/ab00647
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection by green turtles in a spatially heterogeneous benthic landscape in Dry Tortugas National Park, Florida

Abstract: We examined habitat selection by green turtles Chelonia mydas at Dry Tortugas National Park, Florida, USA. We tracked 15 turtles (6 females and 9 males) using platform transmitter terminals (PTTs); 13 of these turtles were equipped with additional acoustic transmitters. Location data by PTTs comprised periods of 40 to 226 d in varying months from 2009 to 2012. Core areas were concentrated in shallow water (mean bathymetry depth of 7.7 m) with a comparably dense coverage of seagrass; however, the utilization di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…In comparison, in Florida, Fujisaki et al. () observed multiple green turtles using the same patch within a foraging site without observing aggression, whereas Bjorndal () reported the absence of aggressive behaviour and no indication of a hierarchy amongst turtles. However, in Shark Bay, Australia, Thomson, Gulick, and Heithaus () recorded multiple aggressive interactions between green turtles, indicating that aggressive behaviour might depend on the availability of forage and resting resources within sites or patches, in addition to the density of turtles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, in Florida, Fujisaki et al. () observed multiple green turtles using the same patch within a foraging site without observing aggression, whereas Bjorndal () reported the absence of aggressive behaviour and no indication of a hierarchy amongst turtles. However, in Shark Bay, Australia, Thomson, Gulick, and Heithaus () recorded multiple aggressive interactions between green turtles, indicating that aggressive behaviour might depend on the availability of forage and resting resources within sites or patches, in addition to the density of turtles.…”
Section: Discussionmentioning
confidence: 99%
“…Various telemetry studies (e.g., radio, satellite, Global Positioning System [GPS]) have also shown that home ranges can extend from <10 to >1,000 km 2 for individuals from any of the seven sea turtle species (Hatase, Omuta, & Tsukamoto, 2007;Seminoff, Resendiz, & Nichols, 2002), depending on species habitat type and proximity to shore, which probably reflects resource quality (Hatase et al, 2007;Seminoff et al, 2002). At finer resolutions, radio and acoustic telemetry studies of green turtles for instance have suggested that daytime foraging is concentrated in defined areas of high resource quality, whereas night-time refuges are located by nearshore reef areas (Brill et al, 1995;Fujisaki, Hart, & Sartain-Iverson, 2016;Makowski, Seminoff, & Salmon, 2006;Seminoff et al, 2002), and this notion is also supported by direct observations (Mortimer & Portier, 1989). In contrast, hawksbills appear to exhibit more complex movements, with some turtles primarily using one area, others using several areas and others exhibiting no clear pattern (Chevis et al, 2016).…”
mentioning
confidence: 99%
“…We captured turtles using both land-based interception of nesting females after nesting and non-nesting emergences, whereupon we restrained them with a portable corral (96.5 cm wide × 67.3 cm height). We also captured turtles using several in-water methods (i.e., hand captures via snorkeling [ 26 ], rodeo or turtle-jumping [ 27 , 28 ]; trawling, and dipnet [ 24 , 29 ]). Upon capture each new turtle was given a passive integrated transponder (PIT) tag in the shoulder or front flipper (Biomark, Boise, ID; models 12 mm tag = BIO12.B.01 V2 PL.SY and 8 mm tag = BIO8.B.03 V1 PL.SY) and individually numbered Inconel flipper tags (National Band and Tag, Newport, KY; model 681) following established protocols (NMFS-SEFSC 2008).…”
Section: Methodsmentioning
confidence: 99%
“…While this technology can be utilized to examine long-distance movements, the most prevalent and useful application for marine turtles is for the study of immature turtle space use within developmental grounds at a finer resolution. While this technology has proven to be valuable when providing insights on the immature turtle home range, space use, and behaviors [31,[42][43][44][45][46][47], there is still much to gain when it comes to understanding marine turtle ecology.…”
mentioning
confidence: 99%